An Initial Review of the Characteristics and Determinants of Female Entrepreneurs in Puerto Rico (2019)
This paper outlines the characteristics and determinants of Puerto Rican female entrepreneurs in 2007. This study utilizes data from the Adult Population Survey (APS) for 2007 from the Global Entrepreneurship Monitor (GEM) Project. We find that female entrepreneurs in Puerto Rico are most likely sole owners of their business establishment, face many local competitors, and do not generally export their goods or services outside of the Island. The primary motivation for business start-up was business opportunism along with a personal goal of greater independence at the workplace. Education serves as a fundamental determinant of female entrepreneurship.